2023
DOI: 10.3390/colloids7020028
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Micelle Formation by the Single Amino Acid-Based Surfactants Undecanoic L-Isoleucine and Undecanoic L-Norleucine in the Presence of Diamine Counterions with Varying Chain Lengths

Abstract: The binding of linear diamine counterions with different methylene chain lengths to the amino-acid-based surfactants undecanoic L-isoleucine (und-IL) and undecanoic L-norleucine (und-NL) was investigated with NMR spectroscopy. The counterions studied were 1,2-ethylenediamine, 1,3-diaminopropane, 1,4-diaminobutane, 1,5-diaminopentane, and 1,6-diaminohexane. These counterions were all linear diamines with varying spacer chain lengths between the two amine functional groups. The sodium counterion was studied as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Another notable difference between the binding of 1,4-diaminobutane and 1,6diaminohexane counterions to the tridecanoic-Glu micelles is that the maximum f b,counterion value for 1,4-diaminobutane was 0.9, while the maximum f b,counterion for 1,6-diaminohexane was 0.6. A similar result was reported by Maynard-Benson, et al in a study of linear diamine counterions binding to undecanoic L-norleucine micelles [17]. Previous studies have shown that these linear diamine counterions bind parallel to the surface of amino acid-based micelles, allowing the two amine function groups to interact with multiple surfactant unimers.…”
Section: Micelle Radii and Counterion Bindingsupporting
confidence: 85%
See 4 more Smart Citations
“…Another notable difference between the binding of 1,4-diaminobutane and 1,6diaminohexane counterions to the tridecanoic-Glu micelles is that the maximum f b,counterion value for 1,4-diaminobutane was 0.9, while the maximum f b,counterion for 1,6-diaminohexane was 0.6. A similar result was reported by Maynard-Benson, et al in a study of linear diamine counterions binding to undecanoic L-norleucine micelles [17]. Previous studies have shown that these linear diamine counterions bind parallel to the surface of amino acid-based micelles, allowing the two amine function groups to interact with multiple surfactant unimers.…”
Section: Micelle Radii and Counterion Bindingsupporting
confidence: 85%
“…These MD simulations are underway. Finally, since R h includes both the micelle and counterions, comparing R h values at pHs where the mole fraction of bound counterions is high to pHs where these values are low provides insight into the structure of the micelle-counterion complex [15][16][17]26]. This method will be employed below to interpret the results shown in Figure 5.…”
Section: Micelle Radii and Counterion Bindingmentioning
confidence: 99%
See 3 more Smart Citations